Legal Aspects In The Establishment of A Village Owned Business Entity Deed And its Business Branches - Elvareta Elen Bayu Permata (Faculty of Law, Merdeka University Surabaya, 2021)
The village is the forerunner to the formation of a government in a unitary state, it can be said that the village is a miniature of a country. There are rights and obligations of village communities, especially in the field of human resource management and natural resources. In carrying out efforts to improve in the economic field, villages can form BUMDESA which has the aim of increasing the income of the villagers. The establishment of BUMDESA can be done through village meetings, if village officials need official documents, it can be made in the form of an authentic deed before a notary in accordance with Article 15 of the Law on Notary Services and its amendments. The type of research in this legal research is normative legal research, which is a process to find the rule of law, legal principles, and legal doctrines in order to answer legal issues faced. Techniques and data collection in this research is carried out by means of library research ( library research). Data collection tools used are document studies to obtain secondary data, by reading, studying, researching, analyzing secondary data, with secondary and tertiary related to this research. The purpose of this legal research is to analyze the legal aspects of the establishment of BUMDES which is made with an authentic deed document. The legal issue in this study is the legal aspect of the establishment of bumdes and other business branches, the second legal issue is the role of a notary in the establishment of a village-owned enterprise business unit. The conclusion of this research is that the village government exists and exists until now since the NKRI was formed, the village has the potential of natural resources that must be managed in an accountable, professional and trustworthy manner. Regarding village management, BUMDESA can be used as a means of driving the economy for the village community. That notaries can assist in making deeds relating to the establishment of BUMDESA and BUMDESA business units.